Melatonin as an Anti-Inflammatory Agent Modulating Inflammasome Activation - Gaia Favero; Lorenzo Franceschetti; Francesca Bonomini; Luigi Fabrizio Rodella; Rita Rezzani (International Journal of Endocrinology)
Inflammation may be defined as the innate response to harmful stimuli such as pathogens, injury, and metabolic stress; its ultimate function is to restore the physiological homeostatic state. The exact aetiology leading to the development of inflammation is not known, but a combination of genetic, epigenetic, and environmental factors seems to play an important role in the pathogenesis of many inflammation-related clinical conditions. Recent studies suggest that the pathogenesis of different inflammatory diseases also involves the inflammasomes, intracellular multiprotein complexes that mediate activation of inflammatory caspases thereby inducing the secretion of proinflammatory cytokines. Melatonin, an endogenous indoleamine, is considered an important multitasking molecule with fundamental clinical applications. It is involved in mood modulation, sexual behavior, vasomotor control, and immunomodulation and influences energy metabolism; moreover, it acts as an oncostatic and antiaging molecule. Melatonin is an important antioxidant and also a widespread anti-inflammatory molecule, modulating both pro- and anti-inflammatory cytokines in different pathophysiological conditions. This review, first, gives an overview concerning the growing importance of melatonin in the inflammatory-mediated pathological conditions and, then, focuses on its roles and its protective effects against the activation of the inflammasomes and, in particular, of the NLRP3 inflammasome.